The impact of cow size on cow-calf and postweaning progeny performance in the Nebraska Sandhills - Ziegler, Robert L (Transl Anim Sci, 2020)
Optimizing beef production system efficiency requires an understanding of genetic potential suitable for a given production environment. Therefore, the objective of this retrospective analysis was to determine the influence of cow body weight (BW) adjusted to a common body condition score (BCS) of 5 at weaning-influenced cow-calf performance and postweaning steer and heifer progeny performance. Data were collected at the Gudmundsen Sandhills Laboratory, Whitman, NE, on crossbred, mature cows (n = 1,607) from 2005 to 2017. Cow BCS at calving, prebreeding, and weaning were positively associated (P < 0.01) with greater cow BW. Increasing cow BW was positively associated (P < 0.01) with the percentage of cows that conceived during a 45-d breeding season. For every additional 100-kg increase in cow BW, calf BW increased (P < 0.01) at birth by 2.70 kg and adjusted 205-d weaning BW by 14.76 kg. Calf preweaning average daily gain (ADG) increased (P < 0.01) 0.06 kg/d for every additional 100-kg increase in cow BW. Heifer progeny BW increased (P < 0.01) postweaning with every additional 100-kg increase in dam BW. Dam BW did not influence (P ≥ 0.11) heifer puberty status prior to breeding, overall pregnancy rates, or the percentage of heifers calving in the first 21 d of the calving season. Steer initial feedlot BW increased by 7.20 kg, reimplant BW increased by 10.47 kg, and final BW increased by 10.29 kg (P ≤ 0.01) for every additional 100-kg increase in dam BW. However, steer feedlot ADG was not influenced (P > 0.67) by dam BW. Hot carcass weights of steers were increased (P = 0.01) by 6.48 kg with every additional 100-kg increase in cow BW. In a hypothetical model using the regression coefficients from this study, regardless of pricing method, cow-calf producers maximize the highest amount of profit by selecting smaller cows. Overall, larger-sized cows within this herd and production system of the current study had increased reproductive performance and offspring BW; however, total production output and economic returns would be potentially greater when utilizing smaller-sized cows.